Composite negative electrode material, preparation method thereof and lithium ion solid-state battery
By mixing the solid electrolyte with the hard carbon precursor and ball milling with Li-Nafion sol to form a composite negative electrode material, the problem of large interface impedance between the solid electrolyte and the negative electrode material in lithium-ion solid-state batteries is solved, and the battery performance is improved.
Patent Information
- Application Number
- CN202510104167.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-23
- Publication Date
- 2025-04-25
AI Technical Summary
In lithium-ion solid-state batteries, the interface impedance between the solid electrolyte and the negative electrode material is relatively large, resulting in battery capacity attenuation and limited application.
By mixing the solid electrolyte with the hard carbon precursor and calcining it, the composite is formed and ball milled with Li-Nafion sol to form a composite negative electrode material to reduce interface impedance and improve electrochemical properties.
While maintaining the electron conductivity, this method improves ionic conductivity, reduces the interface impedance of the "electrode/electrolyte" and improves the overall performance of the battery.
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion solid-state batteries, and in particular to a composite negative electrode material and a preparation method thereof, and a lithium ion solid-state battery. Background Art
[0002] Traditional lithium-ion batteries will trigger internal reactions when overcharged, over-discharged, short-circuited, or thermally abused, leading to thermal runaway, fire, or even explosion. Lithium-ion solid-state batteries replace organic electrolytes with solid electrolytes with outstanding electrochemical and thermal stability, which is expected to solve the safety issues of lithium-ion batteries to a certain extent.
[0003] However, due to the hardness of the solid electrolyte, it is difficult for it to be in close contact with the positive and negative active materials of the battery, resulting in a larger "electrode / electrolyte" interface impedance, especially the interface between the solid electrolyte and the negative electrode. During the charge and discharge process, the stress caused by the volume change of the rigid active material during the cycle can cause the active material particles to break in severe cases, increase the interface impedance, and reduce the battery capacity, limiting the application of lithium-ion solid-state batteries. Summary of the invention
[0004] In order to solve the problem of large interface impedance between solid electrolyte and negative electrode material in the prior art, the present invention provides a method for preparing a composite negative electrode material. The preparation method integrates the solid electrolyte into the hard carbon pore structure to improve the ionic conductivity while maintaining the electronic conductivity, thereby reducing the interface impedance of "electrode / electrolyte", thereby solving the problem of large interface impedance between solid electrolyte and negative electrode material in the prior art.
[0005] The technical solution adopted by the present invention to solve the technical problem is: A method for preparing a composite negative electrode material comprises the following steps: mixing a solid electrolyte with a hard carbon precursor, calcining at 1200-1400°C to generate a composite; and ball milling the composite with Li-Nafion sol to obtain a composite negative electrode material.
[0006] Optionally, the solid electrolyte is a sulfide solid electrolyte.
[0007] Optionally, the sulfide solid electrolyte is Li6PS5Cl.
[0008] Optionally, the sulfide solid electrolyte is prepared by Li2S, P2S5 and LiCl in a molar ratio of 5:1:2.
[0009] Optionally, the mass ratio of the composite to the Li-Nafion sol is (8-10):1.
[0010] Optionally, the Li-Nafion sol is prepared as follows: soaking a Nafion membrane in a LiOH solution at 70-90° C. to obtain a Li-Nafion membrane; placing the Li-Nafion membrane in an N-methylpyrrolidone solvent and heating until the Li-Nafion is dissolved to obtain a Li-Nafion sol.
[0011] Optionally, the hard carbon precursor is starch.
[0012] Optionally, the mass ratio of the hard carbon precursor to the solid electrolyte is (7-12):1.
[0013] Another object of the present invention is to provide a composite negative electrode material, which is prepared by the method for preparing the composite negative electrode material as described above.
[0014] Another object of the present invention is to provide a lithium-ion solid-state battery, comprising the composite negative electrode material as described above.
[0015] The beneficial effects of the present invention are: The present invention provides a preparation method of a composite negative electrode material. By mixing a solid electrolyte with a hard carbon precursor and then calcining them, the solid electrolyte can be compounded into the micropores of the hard carbon, which is equivalent to pre-lithiation of the hard carbon before charging and discharging. To a certain extent, the initial efficiency of the hard carbon can be improved. Furthermore, by ball milling the composite generated by mixing the solid electrolyte with the hard carbon precursor and calcining them with Li-Nafion sol, the introduced Li-Nafion is beneficial to improving the flexibility of the negative electrode material, achieving close contact between the negative electrode material and the solid electrolyte, reducing the interface impedance, and improving the electrochemical performance. DETAILED DESCRIPTION
[0016] The present invention is now further described in detail. The embodiments described below are exemplary and intended to be used to explain the present invention, but cannot be understood as limiting the present invention. All other embodiments obtained by ordinary technicians in this field without creative work based on the embodiments of the present invention belong to the scope of protection of the present invention.
[0017] In order to solve the problem of large interface impedance between solid electrolyte and negative electrode material in the prior art, the present invention provides a method for preparing a composite negative electrode material, which comprises the following steps: mixing a solid electrolyte with a hard carbon precursor, calcining at 1200-1400°C, preferably ball-milling the solid electrolyte and the hard carbon precursor under an inert gas atmosphere for 3-8h, and then calcining at 1200-1400°C, further preferably calcining at 1200°C to generate a solid electrolyte-hard carbon composite, referred to as a composite; ball-milling the composite and Li-Nafion sol in a ball mill, preferably placing the composite and Li-Nafion sol in a ball mill and ball-milling them at a speed of 300 r / min for 10 h to obtain a composite negative electrode material.
[0018] Since the pore structure of hard carbon is relatively large and has almost zero strain during the charge and discharge process, the present invention prefers hard carbon as the negative electrode material for solid-state batteries; further, by mixing the solid electrolyte with the hard carbon precursor and then calcining them, the solid electrolyte can be compounded into the micropores of the hard carbon, which is equivalent to pre-lithiation of the hard carbon before charging and discharging, which can improve the initial efficiency of the hard carbon to a certain extent, and can improve the ionic conductivity while maintaining the electronic conductivity, reduce the interface impedance of the "electrode / electrolyte", and improve the overall performance of the battery; further, by ball-milling the composite generated by mixing the solid electrolyte and the hard carbon precursor and calcining them with Li-Nafion sol, the introduced Li-Nafion is beneficial to improving the flexibility of the negative electrode material, achieving close contact between the negative electrode material and the solid electrolyte, reducing the interface impedance, and improving the electrochemical performance.
[0019] The solid electrolyte may be an inorganic solid electrolyte, a polymer solid electrolyte or an organic-inorganic composite solid electrolyte. Based on the characteristics of sulfide solid electrolytes having high ionic conductivity, high mechanical strength and good flexibility, the present invention preferably uses a sulfide solid electrolyte as the solid electrolyte, and further preferably uses Li6PS5Cl as the sulfide solid electrolyte.
[0020] The preferred sulfide solid electrolyte of the present invention is prepared by Li2S, P2S5 and LiCl in a molar ratio of 5:1:2. Specifically, it is preferably prepared by ball milling Li2S, P2S5 and LiCl in a molar ratio of 5:1:2 under an inert atmosphere, and the ball milling time is preferably 40 hours.
[0021] To ensure electrochemical performance, the present invention preferably has a Li-Nafion sol concentration of 5% (mass fraction), and preferably has a mass ratio of the composite to the Li-Nafion sol of (8-10):1, and more preferably 9:1.
[0022] Furthermore, the Li-Nafion sol is preferably prepared according to the following method: a Nafion membrane is immersed in a LiOH solution at 70-90°C, preferably the concentration of the LiOH solution is 0.5-2 mol / L, and the immersion time is preferably 10-14 hours, to prepare a Li-Nafion membrane through an ion exchange reaction; the Li-Nafion membrane is placed in an N-methylpyrrolidone (NMP) solvent and heated, preferably sealed and then heated in a water bath at 80°C until the Li-Nafion is dissolved to obtain a Li-Nafion sol.
[0023] In the present invention, the Nafion membrane is preferably selected from at least one of Nafion 115, Nafion 117, Nafion 211, Nafion 212, Nafion NR-212, Nafion N324, Nafion N424, and Nafion N438.
[0024] In the present invention, the hard carbon precursor is preferably starch, and further preferably the starch is selected from at least one of cereal starch, potato starch, bean starch and other types of starch.
[0025] Furthermore, when starch is used as the hard carbon precursor, the preparation process includes mixing the solid electrolyte with the hard carbon precursor, sintering at 450-550°C for 8 hours to remove tar, and then heating to 1200-1400°C for calcination.
[0026] In order to ensure the comprehensive performance of the composite negative electrode material, the mass ratio of the hard carbon precursor to the solid electrolyte is preferably (7-12):1, and is further preferably 9:1.
[0027] In summary, the preparation method of the composite negative electrode material provided by the present invention can be prepared according to the following method: S1: First, Li2S, P2S5 and LiCl were ball-milled at a molar ratio of 5:1:2 under inert gas protection for 40 hours to form a mixture 1; S2: According to the formula, the mixture 1 and the hard carbon precursor are ball-milled under the protection of inert gas for 6 hours. After ball-milling, they are sintered at 450-550°C for 8 hours to remove tar, and then heated to 1200-1400°C to generate Li6PS5Cl-hard carbon composite; S3: The Nafion membrane was immersed in a 1 mol / L LiOH solution at 80°C for 12 h to prepare a Li-Nafion membrane through an ion exchange reaction. The Li-Nafion membrane was placed in an N-methylpyrrolidone (NMP) solvent, sealed, and heated in a water bath at 80°C until the Li-Nafion was dissolved to obtain a Li-Nafion sol. S3: According to the formula, Li-Nafion sol and Li6PS5Cl-hard carbon composite were weighed, placed in a ball mill and ball milled at a speed of 300r / min for 10 h to obtain a composite negative electrode material for solid-state batteries.
[0028] Another object of the present invention is to provide a composite negative electrode material, which is prepared by the method for preparing the composite negative electrode material as described above.
[0029] The composite negative electrode material provided by the present invention can be composited into the micropores of the hard carbon by mixing a solid electrolyte with a hard carbon precursor and then calcining the mixture during the preparation process, which is equivalent to pre-lithiation of the hard carbon before charging and discharging, and can improve the initial efficiency of the hard carbon to a certain extent; further, the composite generated by mixing and calcining the solid electrolyte and the hard carbon precursor is ball-milled with Li-Nafion sol, and the introduced Li-Nafion is beneficial to improving the flexibility of the negative electrode material, achieving close contact between the negative electrode material and the solid electrolyte, reducing the interface impedance, and improving the electrochemical performance.
[0030] Another object of the present invention is to provide a lithium-ion solid-state battery, which includes the composite negative electrode material as described above.
[0031] The lithium-ion solid-state battery provided by the present invention adopts a composite negative electrode material. During the preparation process, a solid electrolyte is mixed with a hard carbon precursor and then calcined, so that the solid electrolyte can be compounded into the micropores of the hard carbon, which is equivalent to pre-lithiation of the hard carbon before charging and discharging. To a certain extent, the initial efficiency of the hard carbon can be improved; further, the composite generated by mixing and calcining the solid electrolyte and the hard carbon precursor is ball-milled with Li-Nafion sol, and the introduced Li-Nafion is beneficial to improving the flexibility of the negative electrode material, achieving close contact between the negative electrode material and the solid electrolyte, reducing the interface impedance, and improving the electrochemical performance.
[0032] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, specific embodiments of the present invention are described in detail below.
[0033] Example 1 This embodiment provides a method for preparing a composite negative electrode material, the preparation method comprising the following steps: S1: First, Li2S, P2S5 and LiCl were ball-milled at a molar ratio of 5:1:2 under argon protection for 40 hours to form a mixture 1; S2: The mixture 1 and corn starch were ball-milled at a mass ratio of 1:9 under argon protection for 6 hours. After ball-milling, they were sintered at 450°C for 8 hours to remove tar, and then heated to 1200°C and kept for 6 hours to generate Li6PS5Cl-hard carbon composite. S3: Soak the Nafion212 membrane in a 1 mol / L LiOH solution at 80°C for 12 h to prepare a Li-Nafion membrane through an ion exchange reaction. Place the Li-Nafion membrane in an N-methylpyrrolidone (NMP) solvent, seal it, and heat it in a water bath at 80°C until the Li-Nafion is dissolved to prepare a Li-Nafion sol with a concentration of 5% (mass fraction). S4: 5% Li-Nafion sol and Li6PS5Cl-hard carbon composite were weighed in a mass ratio of 1:9, placed in a ball mill and ball milled at a speed of 300 r / min for 10 h to obtain a composite negative electrode material for solid-state batteries.
[0034] The obtained composite negative electrode material was prepared into a button cell according to the button cell process. The separator used in the button cell was the Li-Nafion membrane prepared in the above step S3. The test was carried out, and the test results are shown in Table 1.
[0035] Example 2 This embodiment provides a method for preparing a composite negative electrode material, the preparation method comprising the following steps: S1: First, Li2S, P2S5 and LiCl were ball-milled at a molar ratio of 5:1:2 under argon protection for 40 hours to form a mixture 1; S2: The mixture 1 and wheat starch were ball-milled at a mass ratio of 1:9 under argon protection for 6 hours. After ball-milling, they were sintered at 550°C for 8 hours to remove tar, and then heated to 1400°C and kept at this temperature for 8 hours to generate a Li6PS5Cl-hard carbon composite. S3: Soak the Nafion117 membrane in a 1 mol / L LiOH solution at 80°C for 12 h to prepare a Li-Nafion membrane through an ion exchange reaction. Place the Li-Nafion membrane in an N-methylpyrrolidone (NMP) solvent, seal it, and heat it in a water bath at 80°C until the Li-Nafion is dissolved to obtain a Li-Nafion sol with a concentration of 5% (mass fraction). S4: 5% Li-Nafion sol and Li6PS5Cl-hard carbon composite were weighed in a mass ratio of 1:9, placed in a ball mill and ball milled at a speed of 300 r / min for 10 h to obtain a composite negative electrode material for solid-state batteries.
[0036] The obtained composite negative electrode material was prepared into a button cell according to the button cell process. The separator used in the button cell was the Li-Nafion membrane prepared in the above step S3. The test was carried out, and the test results are shown in Table 1.
[0037] Example 3 This embodiment provides a method for preparing a composite negative electrode material, the preparation method comprising the following steps: S1: First, Li2S, P2S5 and LiCl were ball-milled at a molar ratio of 5:1:2 under argon protection for 40 hours to form a mixture 1; S2: The mixture 1 and potato starch were ball-milled at a mass ratio of 1:9 under argon protection for 6 hours. After ball-milling, they were sintered at 500°C for 8 hours to remove tar, and then heated to 1400°C and kept warm for 7 hours to generate Li6PS5Cl-hard carbon composite. S3: Soak the Nafion117 membrane in a 1 mol / L LiOH solution at 80°C for 12 h to prepare a Li-Nafion membrane through an ion exchange reaction. Place the Li-Nafion membrane in an N-methylpyrrolidone (NMP) solvent, seal it, and heat it in a water bath at 80°C until the Li-Nafion is dissolved to obtain a Li-Nafion sol with a concentration of 5% (mass fraction). S4: 5% Li-Nafion sol and Li6PS5Cl-hard carbon composite were weighed in a mass ratio of 1:9, placed in a ball mill and ball milled at a speed of 300 r / min for 10 h to obtain a composite negative electrode material for solid-state batteries.
[0038] The obtained composite negative electrode material was prepared into a button cell according to the button cell process. The separator used in the button cell was the Li-Nafion membrane prepared in the above step S3. The test was carried out, and the test results are shown in Table 1.
[0039] Example 4 This embodiment provides a method for preparing a composite negative electrode material, the preparation method comprising the following steps: S1: First, Li2S, P2S5 and LiCl were ball-milled at a molar ratio of 5:1:2 under argon protection for 40 hours to form a mixture 1; S2: The mixture 1 and potato starch were ball-milled at a mass ratio of 1:9 under argon protection for 6 hours. After ball-milling, they were sintered at 550°C for 8 hours to remove tar, and then heated to 1400°C and kept for 6 hours to generate Li6PS5Cl-hard carbon composite. S3: Soak the Nafion NR-212 membrane in a 1 mol / L LiOH solution at 80°C for 12 h to prepare a Li-Nafion membrane through an ion exchange reaction. Place the Li-Nafion membrane in an N-methylpyrrolidone (NMP) solvent, seal it, and heat it in a water bath at 80°C until the Li-Nafion is dissolved to obtain a Li-Nafion sol with a concentration of 5% (mass fraction). S4: 5% Li-Nafion sol and Li6PS5Cl-hard carbon composite were weighed in a mass ratio of 1:9, placed in a ball mill and ball milled at a speed of 300 r / min for 10 h to obtain a composite negative electrode material for solid-state batteries.
[0040] The obtained composite negative electrode material was prepared into a button cell according to the button cell process. The separator used in the button cell was the Li-Nafion membrane prepared in the above step S3. The test was carried out, and the test results are shown in Table 1.
[0041] Example 5 This embodiment provides a method for preparing a composite negative electrode material, the preparation method comprising the following steps: S1: First, Li2S, P2S5 and LiCl were ball-milled at a molar ratio of 5:1:2 under argon protection for 40 hours to form a mixture 1; S2: The mixture 1 and corn starch were ball-milled at a mass ratio of 1:7 under argon protection for 6 hours. After ball-milling, they were sintered at 450°C for 8 hours to remove tar, and then heated to 1200°C and kept for 6 hours to generate Li6PS5Cl-hard carbon composite. S3: Soak the Nafion212 membrane in a 1 mol / L LiOH solution at 80°C for 12 h to prepare a Li-Nafion membrane through an ion exchange reaction. Place the Li-Nafion membrane in an N-methylpyrrolidone (NMP) solvent, seal it, and heat it in a water bath at 80°C until the Li-Nafion is dissolved to prepare a Li-Nafion sol with a concentration of 5% (mass fraction). S4: 5% Li-Nafion sol and Li6PS5Cl-hard carbon composite were weighed in a mass ratio of 1:9, placed in a ball mill and ball milled at a speed of 300 r / min for 10 h to obtain a composite negative electrode material for solid-state batteries.
[0042] The obtained composite negative electrode material was prepared into a button cell according to the button cell process. The separator used in the button cell was the Li-Nafion membrane prepared in the above step S3. The test was carried out, and the test results are shown in Table 1.
[0043] Example 6 This embodiment provides a method for preparing a composite negative electrode material, the preparation method comprising the following steps: S1: First, Li2S, P2S5 and LiCl were ball-milled at a molar ratio of 5:1:2 under argon protection for 40 hours to form a mixture 1; S2: The mixture 1 and corn starch were ball-milled at a mass ratio of 1:12 under argon protection for 6 hours. After ball-milling, they were sintered at 450°C for 8 hours to remove tar, and then heated to 1200°C and kept for 6 hours to generate Li6PS5Cl-hard carbon composite. S3: Soak the Nafion212 membrane in a 1 mol / L LiOH solution at 80°C for 12 h to prepare a Li-Nafion membrane through an ion exchange reaction. Place the Li-Nafion membrane in an N-methylpyrrolidone (NMP) solvent, seal it, and heat it in a water bath at 80°C until the Li-Nafion is dissolved to prepare a Li-Nafion sol with a concentration of 5% (mass fraction). S4: 5% Li-Nafion sol and Li6PS5Cl-hard carbon composite were weighed in a mass ratio of 1:9, placed in a ball mill and ball milled at a speed of 300 r / min for 10 h to obtain a composite negative electrode material for solid-state batteries.
[0044] The obtained composite negative electrode material was prepared into a button cell according to the button cell process. The separator used in the button cell was the Li-Nafion membrane prepared in the above step S3. The test was carried out, and the test results are shown in Table 1.
[0045] Example 7 This embodiment provides a method for preparing a composite negative electrode material, the preparation method comprising the following steps: S1: First, Li2S, P2S5 and LiCl were ball-milled at a molar ratio of 5:1:2 under argon protection for 40 hours to form a mixture 1; S2: The mixture 1 and corn starch were ball-milled at a mass ratio of 1:9 under argon protection for 6 hours. After ball-milling, they were sintered at 450°C for 8 hours to remove tar, and then heated to 1200°C and kept for 6 hours to generate Li6PS5Cl-hard carbon composite. S3: Soak the Nafion212 membrane in a 1 mol / L LiOH solution at 80°C for 12 h to prepare a Li-Nafion membrane through an ion exchange reaction. Place the Li-Nafion membrane in an N-methylpyrrolidone (NMP) solvent, seal it, and heat it in a water bath at 80°C until the Li-Nafion is dissolved to prepare a Li-Nafion sol with a concentration of 5% (mass fraction). S4: 5% Li-Nafion sol and Li6PS5Cl-hard carbon composite were weighed in a mass ratio of 1:8, placed in a ball mill and ball milled at a speed of 300 r / min for 10 h to obtain a composite negative electrode material for solid-state batteries.
[0046] The obtained composite negative electrode material was prepared into a button cell according to the button cell process. The separator used in the button cell was the Li-Nafion membrane prepared in the above step S3. The test was carried out, and the test results are shown in Table 1.
[0047] Example 8 This embodiment provides a method for preparing a composite negative electrode material, the preparation method comprising the following steps: S1: First, Li2S, P2S5 and LiCl were ball-milled at a molar ratio of 5:1:2 under argon protection for 40 hours to form a mixture 1; S2: The mixture 1 and corn starch were ball-milled at a mass ratio of 1:9 under argon protection for 6 hours. After ball-milling, they were sintered at 450°C for 8 hours to remove tar, and then heated to 1200°C and kept for 6 hours to generate Li6PS5Cl-hard carbon composite. S3: Soak the Nafion212 membrane in a 1 mol / L LiOH solution at 80°C for 12 h to prepare a Li-Nafion membrane through an ion exchange reaction. Place the Li-Nafion membrane in an N-methylpyrrolidone (NMP) solvent, seal it, and heat it in a water bath at 80°C until the Li-Nafion is dissolved to prepare a Li-Nafion sol with a concentration of 5% (mass fraction). S4: 5% Li-Nafion sol and Li6PS5Cl-hard carbon composite were weighed in a mass ratio of 1:10, placed in a ball mill and ball milled at a speed of 300 r / min for 10 h to obtain a composite negative electrode material for solid-state batteries.
[0048] The obtained composite negative electrode material was prepared into a button cell according to the button cell process. The separator used in the button cell was the Li-Nafion membrane prepared in the above step S3. The test was carried out, and the test results are shown in Table 1.
[0049] The comparative examples in the present invention are all used for comparison with the scheme in Example 1.
[0050] Comparative Example 1 This comparative example provides a method for preparing a composite negative electrode material, which comprises the following steps: S1: First, Li2S, P2S5 and LiCl were ball-milled at a molar ratio of 5:1:2 under argon protection for 40 hours to form a mixture 1; S2: The mixture 1 and corn starch were ball-milled at a mass ratio of 9:1 under argon protection for 6 hours. After ball-milling, they were sintered at 450°C for 8 hours to remove tar, and then heated to 1200°C and kept warm for 6 hours to generate a Li6PS5Cl-hard carbon composite as a composite negative electrode material; S3: The Nafion212 membrane was immersed in a 1 mol / L LiOH solution at 80°C for 12 h to prepare a Li-Nafion membrane through an ion exchange reaction.
[0051] The composite negative electrode material obtained in step S2 is prepared into a button cell according to the button cell process. The separator used in the button cell is the Li-Nafion membrane prepared in the above step S3. The test is performed and the test results are shown in Table 1.
[0052] Comparative Example 2 This comparative example provides a method for preparing a composite negative electrode material, which comprises the following steps: S1: The corn starch was ball-milled under argon protection for 6 hours, and then sintered at 450°C for 8 hours to remove tar, and then heated to 1200°C and kept at this temperature for 6 hours to generate hard carbon; S2: Soak the Nafion212 membrane in a 1 mol / L LiOH solution at 80°C for 12 h to prepare a Li-Nafion membrane through an ion exchange reaction. Place the Li-Nafion membrane in an N-methylpyrrolidone (NMP) solvent, seal it, and heat it in a water bath at 80°C until the Li-Nafion is dissolved to prepare a Li-Nafion sol with a concentration of 5% (mass fraction). S3: 5% Li-Nafion sol and hard carbon were weighed in a mass ratio of 1:9, placed in a ball mill and ball milled at a speed of 300 r / min for 10 h to obtain a composite negative electrode material for solid-state batteries.
[0053] The obtained composite negative electrode material was prepared into a button cell according to the button cell process. The separator used in the button cell was the Li-Nafion membrane prepared in the above step S2. The test was carried out, and the test results are shown in Table 1.
[0054] Comparative Example 3 This comparative example provides a method for preparing a composite negative electrode material, which comprises the following steps: The corn starch was ball-milled for 6 hours under argon protection, and then sintered at 450°C for 8 hours to remove tar. The temperature was then raised to 1200°C and kept at that temperature for 6 hours to generate hard carbon.
[0055] The obtained hard carbon was prepared into a button cell according to the button cell process. The separator used in the button cell was a PP separator commonly used in lithium batteries. The test was carried out and the test results are shown in Table 1.
[0056] The button cells in the embodiments and comparative examples of the present invention are prepared according to the following method: The negative electrode materials prepared in the above embodiments and comparative examples are respectively used as negative electrode active materials, and are uniformly mixed with polyvinylidene fluoride (PVDF) (dissolved in N-methylpyrrolidone) and conductive carbon black in a mass ratio of 90:5:5, coated into an electrode film, placed in a vacuum drying oven at 120°C for 12 hours, and rolled and punched to obtain a negative electrode sheet; Li-Nafion membrane is used as a button diaphragm, and a metal lithium sheet is used as a counter electrode. The hard carbon negative electrode sheets obtained above are assembled into 2430 button batteries in a glove box, and their electrochemical properties are tested; the test voltage is (0-3)V, and the current is 0.05C.
[0057] Table 1 0.1C gram capacity (mAh / g) First efficiency Capacity retention after 50 cycles Example 1 302 88 99.3 Example 2 297 87 99.2 Example 3 300 89 98.8 Example 4 292 88 99.1 Example 5 285 88 99.2 Example 6 299 83 96.7 Example 7 282 88 98.1 Example 8 291 81 83.8 Comparative Example 1 276 78 90.5 Comparative Example 2 266 72 87.5 Comparative Example 3 251 78 80.1 From the test results, it can be seen that in the technical solution provided by the present invention, the hard carbon contains both pre-lithiated salt Li6PS5Cl and Li-Nafion components, so the gram capacity and initial efficiency, as well as the capacity retention rate after cycling are relatively high.
[0058] The solution provided in Comparative Example 3 directly uses the prepared hard carbon as the negative electrode material, and the gram capacity, initial efficiency and capacity retention rate after cycle are all low.
[0059] Compared with Example 1, Comparative Example 1 lacks the Li-Nafion component, the contact between the negative electrode material and the solid electrolyte is poor, the interface impedance is high, and the overall performance is poor.
[0060] Comparative Example 2 is relative to Example 1. In the absence of electrolyte salt Li6PS5Cl, the hard carbon cannot be pre-lithiated, so the first efficiency is the lowest.
[0061] Based on the above ideal embodiments of the present invention, the relevant staff can make various changes and modifications without departing from the technical concept of the present invention through the above description. The technical scope of the present invention is not limited to the contents of the specification, and its technical scope must be determined according to the scope of the claims.
Claims
1. A method for preparing a composite negative electrode material, characterized in that: The method comprises the following steps: mixing a solid electrolyte with a hard carbon precursor, calcining at 1200-1400°C to generate a composite; and subjecting the composite and Li-Nafion sol to ball milling treatment in a ball mill to obtain a composite negative electrode material.
2. The method for preparing a composite negative electrode material according to claim 1, characterized in that: The solid electrolyte is a sulfide solid electrolyte.
3. The method for preparing the composite negative electrode material according to claim 2, characterized in that: The sulfide solid electrolyte is Li6PS5Cl.
4. The method for preparing the composite negative electrode material according to claim 3, characterized in that: The sulfide solid electrolyte is prepared by using Li2S, P2S5 and LiCl in a molar ratio of 5:1:
2.
5. The method for preparing the composite negative electrode material according to claim 1, characterized in that: The mass ratio of the composite to the Li-Nafion sol is (8-10):
1.
6. The method for preparing the composite negative electrode material according to claim 1, characterized in that: The Li-Nafion sol is prepared as follows: a Nafion membrane is immersed in a LiOH solution at 70-90° C. to obtain a Li-Nafion membrane; the Li-Nafion membrane is placed in an N-methylpyrrolidone solvent and heated until the Li-Nafion is dissolved to obtain a Li-Nafion sol.
7. The method for preparing a composite negative electrode material according to any one of claims 1 to 6, characterized in that: The hard carbon precursor is starch.
8. The method for preparing the composite negative electrode material according to claim 7, characterized in that: The mass ratio of the hard carbon precursor to the solid electrolyte is (7-12):
1.
9. A composite negative electrode material, characterized in that: The composite negative electrode material is prepared by the method for preparing the composite negative electrode material according to any one of claims 1 to 8.
10. A lithium-ion solid-state battery, characterized in that: Comprising the composite negative electrode material as claimed in claim 9.